2021
DOI: 10.1136/bmjopen-2020-044192
|View full text |Cite
|
Sign up to set email alerts
|

Comparing and determining factors associated with hypertension self-care profiles of patients in two multi-ethnic Asian countries: cross-sectional studies between two study populations

Abstract: ObjectivesTo compare the sociodemography, disease characteristics and hypertension self-care profiles and to determine the factors influencing Hypertension Self-Care Profiles (HTN-SCP) in two populations in primary care settings from Singapore and Malaysia.DesignCross-sectional, cross national.SettingMulti-centre, primary care clinics Malaysia and Singapore.Participants1123 adults with hypertension enrolled and analysed.Primary and secondary outcome measuresComparison between sociodemography, disease character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…These scores were higher than that found in this study. However, the proportion of participants with CKD and related complications was not reported by Wee YMS et al 41 . In this study, participants have established complications and may have more complex self-care activities to perform.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These scores were higher than that found in this study. However, the proportion of participants with CKD and related complications was not reported by Wee YMS et al 41 . In this study, participants have established complications and may have more complex self-care activities to perform.…”
Section: Discussionmentioning
confidence: 89%
“…It would be difficult to compare self-care levels across populations without considering various factors like measurement instrument used. In another local primary care study by Wee YMS et al 41 in 2016/17 using the same instrument, the self-care score was reported as 190 (SD 28)…”
Section: Discussionmentioning
confidence: 99%
“…In the quantitative and mixed-method studies, body weight management (29 studies 20 , 24 , 25 , 29 , 30 , 33 , 36 , 39–50 , 52 , 53 , 56–62 , 64 ) and physical exercise (22 studies 21 , 22 , 24 , 30–33 , 35 , 38 , 40–43 , 45 , 47 , 52 , 53 , 56 , 57 , 60 , 61 , 75 ) were the most reported, whereas in the qualitative studies, medication adherence and diet intake was the most reported self-care practice. In addition, a few studies described alternative self-care management methods such as stress-relieving methods (6 studies 35 , 40 , 60 , 66 , 68 , 75 ), sleep and rest (2 studies 68 , 74 ), and spiritual fulfilment was described in one study.…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
“…A study with the largest sample (313,714) was conducted by Nurdiantami et al 24 Sample sizes ranged from 5 to 30 participants in the qualitative studies reviewed. For study settings, in quantitative and mixed-method studies, 10 studies took place nationally, 24,41,[47][48][49][50][51]53,63,64 19 in the urban areas, 20,21,23,[31][32][33][36][37][38]40,42,[44][45][46]52,54,55,58,76 16 in rural areas, 22,[25][26][27][28][29]34,39,43,56,57,[59][60][61][62]75 and two studies in multiple settings. 30,35 For quantitative studies, four of them were conducted in urban settings, …”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation